The Effect of Problem Based Learning Teaching Method on Students’ Critical Thinking Skills in Physics Lesson at SMA Negeri 4 Singaraja - Lisniandila, Ni Putu Ayu; Santyasa, I Wayan; Suswandi, Iwan (JPP (Jurnal Pendidikan dan Pembelajaran), 2018)
Abstract: The study aims to find the effect of problem based-learning method (PBL) on students’ critical thinking skills in a physics course at SMA Negeri 4 Singaraja. The study is a quasi-experiment study with a pretest-posttest nonequivalent control group design. The population of this study was 245 tenth graders majoring in science at SMA 4 Singaraja. The sample of this study was 67 students distributed to two different classes. The data were analyzed by using descriptive analysis and one-way analysis of covariance (ANCOVA). The result of the study shows that there was critical thinking skills gaps between the students using PBL and students using the direct instruction method (DIM). The average score of PBL group had higher average critical thinking skills score (posttest) then the MDI group, in which the scores of PBLM group were in adequate category (M = 54,84; SD = 14,50), meanwhile the scores of DIM group were in low category (M = 43,05; SD = 14,29). Penelitian ini bertujuan mengetahui pengaruh model problem based learning (MPBL) terhadap kemampuan berpikir kritis siswa dalam pembelajaran fisika di SMA Negeri 4 Singaraja. Penelitian ini merupakan penelitian kuasi eksperimen dengan desain pretest-posttest nonequivalent control group design. Populasi penelitian ini adalah siswa kelas X MIPA SMA Negeri 4 Singaraja yang terdiri dari 245 siswa. Pemilihan sampel dalam penelitian ini menggunakan random assignment. Jumlah sampel dalam penelitian ini sebanyak 67 siswa yang terdistribusi dalam dua kelas berbeda. Teknik analisis data yang digunakan adalah analisis deskriptif dan ANAKOVA satu jalur. Hasil penelitian menunjukkan bahwa terdapat perbedaan kemampuan berpikir kritis siswa antara siswa yang berlajar dengan MPBL dan siswa yang belajar dengan MDI. Nilai rata-rata kelompok MPBL memiliki nilai rata-rata kemampuan berpikir kritis (posttest) yang lebih unggul dibanding kelompok MDI yaitu pada kelompok MPBL berada pada kualifikasi cukup (M = 54,84; SD =  14,50) sedangkan kelompok MDI pada kualifikasi rendah (M = 43,05; SD = 14,29).